Tinjauan Kriminologis Tindak Pidana Penganiayaan Berat Terhadap Karyawati Kalbe Farma Di Kota Kupang - kalelena, franklin yulius davidson; Manafe, Deddy R. CH; Dima, Adrianus Djara (Artemis Law Journal, 2023)
According to the 1945 Constitution of the Republic of Indonesia, Amendment IV Article 1 paragraph (3) which reads "The Indonesian State is a state of law", which means that the Indonesian State is based on law (Rechtstaat), not based on mere power (Machstaat). The main problems in this thesis are: (1) What are the factors causing the crime of serious abuse of Kalbe Farma employees in Kupang City? (2) What are the countermeasures carried out by the police in Kupang City? This research is empirical legal research carried out in Kupang City. Data collection techniques use interview techniques and document study. The data used are primary and secondary data. This research was conducted at the Kelapa Lima Kupang Police Sector. The results of data processing were analyzed descriptively qualitatively. Based on the results of the research and discussion, it can be seen: (1) the factors causing the crime of serious abuse of Kalbe Farma employees, namely misunderstanding factors, excessive alcohol consumption factors and environmental factors. (2) the response efforts carried out by the police are preventive efforts. Police efforts in providing legal education to raise public awareness in order to prevent criminal acts from occurring. Repressive efforts. Efforts made when a criminal act has occurred in the nature of taking action against the perpetrator of the crime.